The Impact of Executive Compensation on Real Earnings Management - A Case Study of Chinese Listed Companies - HU, XIAOJIE (2022)
Financial reporting is increasingly becoming a focus of attention in the development of capital markets. The importance of accounting earnings information is also becoming more and more prominent as it provides the basis for economic decisions made by shareholders, creditors and other stakeholders of the company, and his importance is becoming more and more prominent. Real earnings management is the manipulation of corporate sales revenue, production costs and discretionary expenses through the construction of real trading activities for specific purposes, which are relatively hidden, difficult to detect and materially harmful to the business. In a business, the separation of ownership and operation of the business can lead to an inconsistency of interests between the principal and the agent, resulting in agency problems. This can be mitigated by a policy of compensation incentives for executives to maximize their own interests and reduce the likelihood of earnings management. This paper uses pay incentives for executives as an entry point to explore the impact of executive pay levels and the executive pay gap on true earnings management. Data from listed companies in the SSE 50 and FTSE 50 from 2018-2020 are selected to study the impact of executive compensation on real earnings management. The test results show that both executive pay level and executive pay gap are negatively related to the level of real earnings management, the higher the level of executive pay, the lower the level of real earnings management, and the larger the executive pay gap, the lower the level of real earnings management, indicating that the remuneration incentive mechanism in China plays a significant role The higher the level of executive compensation, the lower the level of real earnings management. The negative relationship between executive compensation, executive pay gap and real earnings management is more pronounced in state-owned enterprises than in non-state-owned enterprises, probably because senior managers in non-state-owned enterprises need to maximize corporate profits and face less pressure from the state and society to regulate them harshly. Keywords: real earnings management; executive pay levels; executive pay gap; nature of the business